Remuneration Information System Success In State University As Legal Entity (PTN-BH) Using Delone and Mclean Model - Jaqolina Anggraeni Vigim (AKRUAL: JURNAL AKUNTANSI, 2019)
This study aimed to determine the success of remuneration information systems in PTN-BH using the DeLone and McLean models. The sampling method used was simple random sampling with 51 of 101 work units at the Indonesia University of Education. The data used were primary data with questionnaires, documentation, and interview techniques. Hypothesis testing was done by using version 3.0 Partial Least Square (PLS) software. The results of hypothesis testing show that the quality of the system influences user satisfaction, the quality of information affects user satisfaction and user satisfaction affects the personal impact.